2008
DOI: 10.1007/s11211-008-0077-9
|View full text |Cite
|
Sign up to set email alerts
|

Legitimacy Crisis? Behavioral Approach and Inhibition When Power Differences are Left Unexplained

Abstract: Possessing social power leads to approach-related affect and behavior, whereas lacking power leads to inhibition (Keltner, Gruenfeld, & Anderson, Psychol Rev 110:265-284, 2003). However, such effects should be moderated by whether an explanation is given for these power differences. Participants were assigned to a low-power or high-power role and then interacted with a confederate in the opposite role. Participants were told these role assignments were made for legitimate (expertise) or illegitimate (nepotism)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Previous research on psychological power has identified legitimacy as a moderator of the effects of psychological power on agentic behavior (Lammers, Galinsky, Gordijn, & Otten, 2008;Smith, Jost, & Vijay, 2008). Arguing that illegitimacy changes the fundamental nature of power-based hierarchical relationships, Lammers et al (2008) noted that legitimate power entails cooperation: the powerful rule and the powerless comply.…”
Section: The Link From Structure To Sense Of Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on psychological power has identified legitimacy as a moderator of the effects of psychological power on agentic behavior (Lammers, Galinsky, Gordijn, & Otten, 2008;Smith, Jost, & Vijay, 2008). Arguing that illegitimacy changes the fundamental nature of power-based hierarchical relationships, Lammers et al (2008) noted that legitimate power entails cooperation: the powerful rule and the powerless comply.…”
Section: The Link From Structure To Sense Of Powermentioning
confidence: 99%
“…This dynamic changes the likely relationship between power and agentic behavior: the powerless are more likely to act to overthrow the powerful, and the powerful are made aware of the instability of their structural power, evoking a sense of powerlessness and paralysis. As a consequence, Lammers et al (2008) argue and empirically demonstrate, when power is illegitimate, the effects of power on action reverse (see also Hays & Goldstein, 2015;Lammers, Galinsky, Gordijn, & Otten, 2012;Smith et al, 2008;Willis et al, 2010).…”
Section: The Link From Structure To Sense Of Powermentioning
confidence: 99%
“…However, these studies often treat power and status as if the distinctions between them do not matter. Scholars often use these terms interchangeably (e.g., Conway, Pizzamiglio, & Mount, 1996;Hall, Coats, & LeBeau, 2005;Smith, Jost, & Vijay, 2008), suggesting that they may simply be different terms for labeling a single construct. In other cases, researchers have conceptually distinguished power and status, but empirically focused on comparisons within one dimension, without measuring the other (e.g., Fragale, Rosen, Xu, & Merideth, 2009;Weick & Guinote, 2008), or have compared individuals who are high in both power and status to those who are low on both dimensions (e.g., Anderson & Berdahl, 2002;Galinsky et al, 2003).…”
Section: Status Versus Power: Similarities and Distinctionsmentioning
confidence: 99%
“…Even when participants experience low-and high-power roles in the laboratory, these roles generally do not involve real decisions or consequential outcomes (13). Because the effects of power are known to change when power involves meaningful interpersonal interactions versus hypothetical scenarios or anticipated interactions (14), and when power differences are experienced as appropriate and legitimate versus arbitrarily assigned (15,16), it is not a given that theories developed in the experimental laboratory will generalize to real-world power experiences. Furthermore, if power operates in aspects of life beyond work, it is important to determine if theories of power (3,4) hold true across all these contexts, such as family relationships involving more complicated power dynamics (8).…”
mentioning
confidence: 99%